The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1679-62252009000200018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, seasonal and ontogenetic variation in the diet of Astyanax aff. fasciatus (Ostariophysi: Characidae) in an Atlantic Forest river, Southern Brazil

Abstract: This study described the feeding habits of the characin Astyanax aff. fasciatus. The diet compositions of specimens from two sites (A and B) on a river in Southern Brazil were compared according to the size of individuals and seasonal period. The collections were performed monthly from March 2005 to February 2006, where the stomach contents of 290 specimens were assessed. Food items for A. aff. fasciatus were basically composed of plants and insects, especially leaf fragments, seeds, fruits, filamentous algae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
4
16
0
1
Order By: Relevance
“…In the Mato Grosso stream Astyanax taeniatus had a varied diet. Distinct feeding behaviour with high plasticity has been previously described for this genus (Costa, 1987;Cassemiro et al, 2002;Gomiero and Braga, 2003;Borba et al, 2008;Wolff et al, 2009). In this study, and in another by Bennemann et al (2005), the diet of Astyanax species was found to consist primarily of allochthonous insects and terrestrial plant debris, and changes in the consumption of these resources were related to physical changes in the environment.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the Mato Grosso stream Astyanax taeniatus had a varied diet. Distinct feeding behaviour with high plasticity has been previously described for this genus (Costa, 1987;Cassemiro et al, 2002;Gomiero and Braga, 2003;Borba et al, 2008;Wolff et al, 2009). In this study, and in another by Bennemann et al (2005), the diet of Astyanax species was found to consist primarily of allochthonous insects and terrestrial plant debris, and changes in the consumption of these resources were related to physical changes in the environment.…”
Section: Discussionsupporting
confidence: 70%
“…This is also seen in other species of the Characidae family (e.g. Barreto and Aranha, 2006;Wolff et al, 2009;Mazzoni et al, 2010a), indicating that the relationship between intestine length and the standard length of a species varies during the growth of an individual (Mazzoni et al, 2010a). The intestinal quotient (Qi) can be a useful tool for evaluating ontogenetic variations in the diet of fish (Zavala-Camim, 1996), and an increase in the intestinal quotient of adults may be associated with high plasticity, the capacity for food spectrum expansion (Andrian et al, 2001) and the utilization of less digestible (e.g.…”
Section: Discussionsupporting
confidence: 55%
“…This high similarity between local and broader spatial distributions could be explained by: i) lacking larger migratory species in Iguaçu River basin that are deeper channel dwellers in the Paraná River and others tributaries (Agostinho et al 2003(Agostinho et al , 2008; ii) the wide ability of the characins of genus Astyanax to colonize practically all environments of basin, including large and small inland water or even reservoirs. This genus present broad distribution in low Iguaçu River basin (Garavello & Sampaio 2010), pronounced trophic plasticity (Wolff et al 2009, and were captured here, with high abundances in all streams independently of physiographic features and land use.…”
Section: Discussionmentioning
confidence: 54%
“…Such is the case for surface Astyanax. A surface population studied by Wolff et al (2009) showed that in fish of less than 5 cm standard length, 75.8% of their diet by volume was made of animal items. In 5.1 to 7.5 cm long fish, animal content decreased to 28.6%, and when longer than 7.6 cm, its animal derived diet was reduced to 20.7% to the increase of plant items.…”
Section: Discussionmentioning
confidence: 99%